Antibacterial Activity Of Δ-Guaiene Patchouli Oil Against Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATCC 27853 - Tania Rizki Fauziah (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
Patchouli oil known as the main ingredient in fragrances such as perfume, bath soap and hair oil. Not only that, this oil is also known to have antibacterial, antifungal, antiemetic, and trypanocidal activity. One of the highest content of patchouli oil is Δ-guaiene. Δ-guaiene is one of the sesquiterpene groups. The sesquiterpene compounds present in essential oils have microbial and larvicidal activity. The sesquiterpene antibacterials work by affecting the permeability and protein membrane activity of these microorganisms. The purpose of this study was to determine the antibacterial activity of Δ-guaiene of patchouli oil againstEscherichia coli and Pseudomonas aeruginosa. This antibacterial test was carried out by the well diffusion method at various concentrations (20%, 40%, 60%, 80%, and 100% v/v) to determine the diameter of the inhibitory power. The results of this study indicate that the largest zone of inhibition was found at a concentration of 80% for Escherichia coli and 100% for Pseudomonas aeruginosa.